How women have fared with the rise of the People Republic of China in Global Supply Chain Trade. - Wang, Limin (Metro Manila, Philippines Asian Development Bank, 2017)
The analysis shows global integration through trade expansion improved the concentration of men and women equally in professional and skilled occupations and in management positions but increased employment in manufacturing for global supply chain trade faster for women than men. This led to relative income gains for women, which in turn decreased the male female sex ratio among those aged 04 years. Gender specific policies like higher education and skills training for professional and leadership positions complemented with private sector incentives for female employment can promote gender equality.
Keywords: Gender equality -- China; Economic policy -- China; Electronic books